2020
DOI: 10.3390/brainsci10040235
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Transcranial Direct Current Stimulation Improves Maximum Isometric Force Production during Isometric Barbell Squats

Abstract: Maximum voluntary contraction force (MVC) is an important predictor of athletic performance as well as physical fitness throughout life. Many everyday life activities involve multi-joint or whole-body movements that are determined in part through optimized muscle strength. Transcranial direct current stimulation (tDCS) has been reported to enhance muscle strength parameters in single-joint movements after its application to motor cortical areas, although tDCS effects on maximum isometric voluntary contraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 73 publications
1
12
1
Order By: Relevance
“…Similarly, Kamali et al [ 42 ] have reported not only beneficial effects on sEMG signal after the application of a-tDCS (2 mA) for 13 min on the primary motor cortex (M1) and temporal cortex (TC) in bodybuilders, but also an improvement in performance (muscular strength and endurance). These improvements on neuromuscular performance have also been confirmed in previous research conducted in other types of muscle contractions, such as an isometric squat, where significant improvements in MVIC were shown [ 43 ]. Similar results have been reported in the biceps brachii muscles [ 41 ].…”
Section: Discussionsupporting
confidence: 78%
“…Similarly, Kamali et al [ 42 ] have reported not only beneficial effects on sEMG signal after the application of a-tDCS (2 mA) for 13 min on the primary motor cortex (M1) and temporal cortex (TC) in bodybuilders, but also an improvement in performance (muscular strength and endurance). These improvements on neuromuscular performance have also been confirmed in previous research conducted in other types of muscle contractions, such as an isometric squat, where significant improvements in MVIC were shown [ 43 ]. Similar results have been reported in the biceps brachii muscles [ 41 ].…”
Section: Discussionsupporting
confidence: 78%
“…First, we observed significantly worse performance in the Rotarod test and the Vertical ladder (90°) test in TAAR5-KO mice, which may be the consequence of the decrease in muscle strength or endurance in this group. It has been shown that muscle strength may depend in part on cerebellar function and can be modulated through the cerebellar neural pathways 30 . A likely reason for the sensorimotor characteristics changes observed in TAAR5-KO animals could be the alterations in the functioning of classical monoaminergic systems 17 , 27 , particularly in histaminergic projections of the cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…Easily acquired continuous measurements are not always helpful when the signal has lowdelity, or when the data is not the most relevant for the task in question [113]. [607], testosterone assay for both acute exercise-induced response and global levels [288,484], muscle oxygenation with fNIRS [679], ultrasound SWE for the (real-time) quantication of musculotendon stiness [419,467], cartoon of smart insoles for quantifying center-of-pressure (CoP) and the tripod loading , force plates for measuring ground reaction forces [245], EMG for measuring activation [257] (myoelectric activity more exactly [841]), sweat-based biochemical sensing for detecting metabolic and neuromuscular fatigue from ammonia and lactate levels [697], core body temperature for circadian phase [788] and muscle temperature measurements for training preparedness, subjective rating of eort through RPE logging (https://www.reactivetrainingsystems.com/), cognitive load from electrical (EEG) [396] and hemodynamic (fNIRS) brain activity [395]. Image from Dr. Ben Pollock, reproduced with permission.…”
Section: Precision Strength Trainingmentioning
confidence: 99%